Returns: Back Stitch Methodology as a Reflective Approach to Artistic Research - Maier, Danica; Brown, Andrew; Lee, Joanne; Stevens, Christine (Research in Arts and Education, 2024)
This paper explores the ongoing investigation by the artist-researcher group Returns, revisiting the Spode ceramics factory in Stoke-on-Trent, England, and broader post-industrial settings. This paper describes and reflects upon the group’s ‘back stitch’ methodology (derived from embroidery), valuing the hidden under-thread that reinforces and sustains the investigation. Through collaborative dialogue, the group uses the back stitch to produce momentum by returning ‘backwards into the beneath’. The paper considers how the back stitch methodology can slow investigations to deepen understanding, enable rhizomatic complexity and support the critical potential for a community of artistic scholarship and research evidenced through the individual’s practice.